Protocol for mpox virus inactivation in containment level 3 for safe handling of animal samples - Benedicte Mpia Moni; Arianna Mahely Hurtado-Monzón; Jill Van Kessel; Robert A. Kozak; Antonio Facciuolo; Arinjay Banerjee; Anil Kumar (STAR Protocols)
Summary: High biocontainment is required to handle infectious mpox virus (MPXV) specimens, which can hinder research and diagnostic efforts during outbreaks. Here, we present a protocol for inactivating MPXV-contaminated animal samples using commercial lysis buffers. We describe steps for virus propagation and quantification and MPXV inactivation. We then detail procedures for validating the inactivation using a cell-based technique and qPCR. This protocol provides a framework for safely managing MPXV in lower-containment laboratories, facilitating downstream applications and improved outbreak management. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.